1998
DOI: 10.1001/archsurg.133.4.406
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Follow-up of Prophylactic Vena Cava Filters in High-Risk Trauma Patients

Abstract: Objective: To assess the short-and long-term outcomes of vena cava filter (VCF) placement for prophylaxis against pulmonary embolism in patients at high risk due to trauma.Design and Setting: Case series at a level I trauma center.Patients: Patients were considered for prophylactic VCF placement if they met 1 of the injury criteria-spinal cord injuries with neurologic deficit, severe fractures of the pelvis or long bone (or both), and severe head injuryand had a contraindication to anticoagulation.Intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(69 citation statements)
references
References 21 publications
1
64
0
4
Order By: Relevance
“…Tilt was found to be the most common cited cause for failure to retrieve filters (5). Rogers et al found that filters tilted greater than 14 degrees had an association with an increase in PE and recommended addition of a second filter for adequate prophylaxis (7,13). Studies on Greenfield IVC filters (Boston Scientific, Natick, MA, USA) showed an incidence of tilt in 5% of © Cardiovascular Diagnosis and Therapy.…”
Section: Filter Tiltmentioning
confidence: 99%
“…Tilt was found to be the most common cited cause for failure to retrieve filters (5). Rogers et al found that filters tilted greater than 14 degrees had an association with an increase in PE and recommended addition of a second filter for adequate prophylaxis (7,13). Studies on Greenfield IVC filters (Boston Scientific, Natick, MA, USA) showed an incidence of tilt in 5% of © Cardiovascular Diagnosis and Therapy.…”
Section: Filter Tiltmentioning
confidence: 99%
“…2) (Ando & Kuribayashi, 2000;Boston Scientific, 2007;Greenfield et al, 1990Greenfield et al, , 1991Kinney et al, 1997;Nara et al, 1995;Rogers et al, 1998;Streiff, 2000;Swaminathan et al, 2006). This permanent filter is commonly used in Japan.…”
Section: Filter Modelmentioning
confidence: 99%
“…Moreover, the filter should not move in the blood vessel after deployment and should pass smoothly through the slim introducer catheter. Although insertion appears to be a safe and effective method by which to prevent the recurrence of pulmonary embolism, patients in whom the filter has become tilted may experience pulmonary embolism recurrence because of a decrease in the thrombus-trapping performance of the filter (Nara et al, 1995;Rogers et www.intechopen.com al., 1998). In order to satisfy these requirements, several types of filters, such as permanent, temporary, and retrievable filters, have been proposed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A inclinação do filtro de Greenfield na veia cava não é uma complicação freqüente, ocorrendo entre 5,5 a 10% dos casos 14,15 . Entretanto, quando ocorre, está associada à perda da eficiência na captura de êmbolos 3,16 , além de favorecer a extrusão das hastes 17 , as quais, por sua vez, podem provocar a perfuração de estruturas vizinhas à veia cava, como ureter, vísceras e aorta 18 .…”
Section: Introductionunclassified